Targeted Intraoperative Radiotherapy Is Non-inferior to Conventional External Beam Radiotherapy in Chinese Patients With Breast Cancer: A Propensity Score Matching Study - Mi, Yin; Lv, Pengwei; Wang, Fang; Li, Lin; Zhu, Mingzhi; Wang, Yanyan; Zhang, Yingying; Liu, Lele; Cao, Qinchen; Dong, Meilian; Shi, Yonggang; Fan, Ruitai; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate the efficacy of targeted intraoperative radiotherapy (TARGIT) versus conventional external beam radiotherapy (EBRT) in Chinese patients with breast cancer. Methods: We retrospectively analysed breast cancer patients who underwent breast-conserving surgery (BCS) at our hospital between April 2009 and October 2017. Patients were divided into TARGIT group and EBRT group according to different radiotherapy methods. TARGIT was performed with low-energy X-rays emitted by the Intrabeam system to deliver a single dose of 20 Gy to the applicator surface. Propensity score matching was performed at 1:1. The Kaplan-Meier method was used to calculate the locoregional recurrence (LR), distant metastasis-free survival (DMFS), disease-free survival (DFS), and overall survival (OS) of the two groups, and the log-rank test was run to analyse between-group difference before and after matching. Results: A total of 281 patients were included, with a median follow-up of 43 months. Of them, 82 were included in the TARGIT group and 199 in the EBRT group. Using the risk-adapted approach, 6.1% of patients received supplemental EBRT in the TARGIT group. The 5-year LR rate was 3.2% in the TARGIT group and 3.1% in the EBRT group (P = 0.694), the 5-year DMFS rates were 100% and 96.7%, respectively (P = 0.157); the 5-year DFS rates were 96.8% and 94.2% (P = 0.604); and the 5-year OS rates were 97.6% and 97.8% (P = 0.862). After matching which eliminated interference from imbalanced baseline factors, 128 matched patients were analysed by the Kaplan-Meier method. The 5-year LR rate was 2.3% in the TARGIT group and 1.6% in the EBRT group; the 5-year DMFS rates were 100% and 98.4%, respectively; the 5-year DFS rates were 97.7% and 98.4%; and the 5-year OS rates were 98.4% and 98.4% (P = 0.659, 0.313, 0.659, 0.987). There was no significant difference in efficacy between TARGIT group and EBRT group. Conclusion: TARGIT and EBRT have similar 5-year outcomes in selected Chinese breast cancer patients undergoing BCS, and it can be used as an effective alternative to standard therapy, with substantial benefits to patients. The results need to be further confirmed by extending the follow-up time.